SISTEM PENGOLAHAN JADWAL KEBERANGKATAN DAN PEMESANAN TIKET PT. ALMASAR BERBASIS WEB - David Adiamanta; Parasian D.P Silitonga (UPPM, 2019)
PT. Almasar is a land transportation service company whose main activity is to takepassenger to their destination safely and try to rovide the best service possible during thetrip. Provision of information that is fast, precise, and accurate is currently very muchneeded and is one of the drivers of increasing work outcomes for each compony. Ticket salesat PT. Almasar are still being held at the ticket window. This resulted in prospectivepassenger having to spend more time ordering tickets and the lack of information PT.Almasar obtained of community . In this thesis , a Web-based Bus Departure And SalesSchedule System was build which was designed using the PHP 5.0 Programing language.In designing a database using MySQL application , for web server using Apace,while foreditor using Macromedia Dreamweaver 8.